Reduced complications and mortality after admission for head and neck cancer in patients with previous dental scaling: a retrospective cohort study based on real-world data - Che-Hsuan Lin; Chuen-Chau Chang; Hsun-Hua Lee; Yi-Sheng Chou; Chia-Yen Lee; Chun-Chieh Yeh; Ta-Liang Chen; Chien-Chang Liao (PLoS ONE, 2025)
Background The association between oral health and cancer outcomes remains unclear. The purpose of this study was to evaluate the complications and mortality after admission of head and neck cancer (HNC) in patients with and without dental scaling (DS). Methods We used data from public health insurance and identified 121,973 patients with admission of HNC aged ≥ 18 years who received inpatient care in 2006–2020. The outcomes during the admission of HNC were compared between patients who had received DS or not within the previous 24 months before admission. The adjusted odds ratios (HRs) and 95% confidence intervals (CIs) of complications and mortality associated with DS were analyzed in the multivariate Cox proportional regression models. Results We found that DS was significantly associated with reduced risks of septicemia (OR 0.84, 95% CI 0.81–0.88), stroke (OR 0.87, 95% CI 0.80–0.95), pneumonia (OR 0.88, 95% CI 0.84–0.91), urinary tract infection (OR 0.88, 95% CI 0.80–0.97), and 30-day in-hospital mortality (OR 0.88, 95% CI 0.85–0.92). Compared with HNC patients without DS, HNC patients with DS had a shortened length of hospital stay (p < 0.0001), decreased medical expenditures (p < 0.0001), and reduced risks of intensive care (OR 0.92, 95% CI 0.89–0.95) after admission of HNC. Conclusion In conclusion, we suggested that HNC patients who received DS had reduced complications and mortality compared with those without DS. It is essential to interpret this association with caution due to the confounding factors involved. Our study implied the possibility that clinical physicians may encourage HNC patients to receive regular DS.